Atomically Dispersed Mn for Electrochemical CO2 Reduction with Tunable Performance. Issue 24 (14th November 2022) - Yao, Zhibo; Zhan, Xinyu; Ruan, Yukun; Li, Weixiang; Xu, Yiwen; Chen, Yuxin; Robertson, Alex W.; Tao, Ranting; Hong, Song; Hao, Leiduan; Sun, Zhenyu
Abstract: Electrochemical CO2 reduction (ECR) is recognized as a sustainable and promising approach for the production of high‐value chemicals. To facilitate widespread application of this technology, the design and construction of efficient cathodic electrocatalysts is critically important. Here we report the synthesis of atomically dispersed manganese on nitrogen‐doped porous carbon (Mn SAs/NC) using a facile and scalable annealing method for catalyzing the ECR reaction. The as‐obtained Mn SAs/NC delivers high activity and selectivity toward CO formation with a faradaic efficiency of 80.5±0.6%, over 5 times that of bare NC. The high activity is preserved even after 10 h of continuous polarization. The catalytic properties of our cost‐effective Mn SAs/NC catalyst are readily tuned by regulating the nitrogen configurations and the percentage of Mn SAs via modulation of the nitrogen precursor and the thermal treatment conditions. Abstract : We demonstrate a simple and scalable method for the synthesis of Mn single atoms supported on nitrogen‐doped carbon for tunable and efficient electrocatalytic CO2 reduction reaction to yield CO.